Sophie Assiniway / Grace Chandler Horn - Horn, Grace Chandler, photographer. (William L. Clements Library, 1900)
Full length portrait of Sophie Assiniway wearing western clothing standing in pumpkin patch near home in Middle Village, Michigan. Lacking mount.; Blindstamp: Grace Chandler Horn.; Contemporary inscription on verso: Fasquelle.; Title devised by cataloger.; "Sophie Assiniway" variant personal names: Sophia Assinaray, Sophia Pagowiah, Sophie Assinaray, Sophie Assinaway.; "Ottawa Indians" variant names: Anishinaabe, Odawa Indians, Outaouak Indians, Tawa Indians.